PROFIL SOSIAL EKONOMI PENYELAM LOKAN (POLYMESODA) DI KANAGARIAN INDERAPURA BARAT KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - Kristi, Nolinda Nada (STKIP PGRI Sumbar, 2014)
This research is motivated by the presence of divers seashell in the Western District of beheading Kenagarian Problem Inderapura South Coastal District . Increased income seashell divers bring good influence on the economic life of the people than to work the rice fields . This type of research is qualitative . Respondents in this study is a seashell divers in the Western District of beheading Kenagarian Problem Inderapura South Coastal District . Informants in this study were taken by snowball ( snowball ) . The instrument used in this study is in the form of interviews .The results of this study found : 1 ) the condition of the diver revenue Kenagarian seashell in the Western District of beheading Problem Inderapura South Coastal District revenues included in the category of moderate income . 2 ) the state of education in the seashell divers Kenagarian Inderapura Western District of South Coastal District Problem beheaded in public junior high school graduation . 3 ) health condition seashell divers in the Western District of beheading Kenagarian Problem Inderapura South Coastal District is generally a mild disease . 4 ) livelihood seashell divers side in Kenagarian Inderapura Western District of South Coastal District beheading Problem is farming because farming requires a long time to get results .